2010
DOI: 10.1371/journal.pone.0013598
|View full text |Cite
|
Sign up to set email alerts
|

N-P Co-Limitation of Primary Production and Response of Arthropods to N and P in Early Primary Succession on Mount St. Helens Volcano

Abstract: BackgroundThe effect of low nutrient availability on plant-consumer interactions during early succession is poorly understood. The low productivity and complexity of primary successional communities are expected to limit diversity and abundance of arthropods, but few studies have examined arthropod responses to enhanced nutrient supply in this context. We investigated the effects of nitrogen (N) and phosphorus (P) addition on plant productivity and arthropod abundance on 24-yr-old soils at Mount St. Helens vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 65 publications
3
43
2
Order By: Relevance
“…Here, high management intensity positively affected the number of grasshopper individuals, supporting published findings (Drummond et al, 2008;Bishop et al, 2010), whereas other studies showed a decrease of grasshopper individuals in fertilization treatments mediated by changes in the vegetation structure (Wingerden et al, 1992;Marini et al, 2008). Vegetation structure is an important parameter for grasshoppers in large-scale habitats (Morris, 2000), but is of minor importance for experiments at smaller scales (such as ours), where patches of different vegetation structure are in close vicinity.…”
Section: Grasshopperssupporting
confidence: 85%
“…Here, high management intensity positively affected the number of grasshopper individuals, supporting published findings (Drummond et al, 2008;Bishop et al, 2010), whereas other studies showed a decrease of grasshopper individuals in fertilization treatments mediated by changes in the vegetation structure (Wingerden et al, 1992;Marini et al, 2008). Vegetation structure is an important parameter for grasshoppers in large-scale habitats (Morris, 2000), but is of minor importance for experiments at smaller scales (such as ours), where patches of different vegetation structure are in close vicinity.…”
Section: Grasshopperssupporting
confidence: 85%
“…Apple et al (2009) found that naturally occurring foliar P levels were positively correlated with caterpillar survival and growth rate at an early primary succession terrestrial habitat. At this same site, Bishop et al (2010) also documented that P addition promoted orthopteran abundance (primarily Melanoplus spp.…”
Section: Discussionmentioning
confidence: 67%
“…This contention is supported by experimental tests of plant nutrient limitation (Bishop et al, 2010;Elser et al, 2007) and correlations between host plant P content and grasshopper abundance (Joern et al, 2012). Indeed, P levels in terrestrial foliage range widely.…”
Section: Introductionmentioning
confidence: 94%
“…However, Joern et al (2012) found that plant P content was the most important element predicting overall grasshopper abundance in the central Nebraskan grasslands. Moreover, fertilization of natural plants with P directly stimulates growth and population density of a variety of insects, including Orthopterans on Mount St Helens volcano (Bishop et al, 2010). For monophagous or limited-mobility insects, limitations by dietary P may be more likely and prevalent (Apple et al, 2009;Perkins et al, 2004).…”
Section: Relevance For Field Conditionsmentioning
confidence: 99%